Functional expression of the GABAA receptor α2 and α3 subunits at synapses between intercalated medial paracapsular neurons of mouse amygdala - Geracitano, Raffaella; Fischer, David T.; Kasugai, Yu; Ferraguti, Francesco; Capogna, Marco (Frontiers in Neural Circuits, 2012)
In the amygdala, GABAergic neurons in the intercalated medial paracapsular cluster (Imp) have been suggested to play a key role in fear learning and extinction. These neurons project to the central amygdaloid nucleus and to other areas within and outside the amygdala. In addition, they give rise to local collaterals that innervate other neurons in the Imp. Several drugs, including benzodiazepines, are allosteric modulators of GABA-A receptors. Benzodiazepines have both anxiolytic and sedative actions, which are mediated through GABA-A receptors containing alpha2/3 and alpha1 subunits, respectively. To establish whether alpha1 or alpha2/3 subunits are expressed at Imp cell synapses, we used paired recordings of anatomically-identified Imp neurons and high resolution immunocytochemistry in the mouse. We observed that a selective alpha3 subunit agonist, TP003 (100 nM), significantly increased the decay time constant of the unitary IPSCs. A similar effect was also induced by zolpidem (10 microM) or by diazepam (1 microM). In contrast, lower doses of zolpidem (0.1-1 microM) did not significantly alter the kinetics of the unitary IPSCs. Accordingly, immunocytochemical experiments established that the alpha2 and alpha3, but not the alpha1 subunits of the GABA-A receptors, were present at Imp cell synapses of the mouse amygdala. These results define, for the first time, some of the functional GABA-A receptor subunits expressed at synapses of Imp cells. The data also provide an additional rationale to prompt the search of GABA-A receptor alpha3 selective ligands as improved anxiolytic drugs.